Categorías esenciales del humanismo cristiano (2014)
In this historic moment, more than in any other time or era, there is a need for Wisdom to humanize the world, from both human and divine vocation. This articule, is dimensioned in two essencial categories, human and divine, both which are identified within the writtings of professor Rodrigo Noguera Laborde, founder of the Sergio Arboleda University. Following the footsteps of thinkers, philosophers and theologist that support the proclamation of a theocentric humanism, permits to visualize the pillars on which the wisdom structure of humanism is built for this century. The revelation of these categories puts man in this world as created by Gods love, pinnicule center,lord of creation and dignified by his racional capacity, conscience, soul or spirit. Likewise able to interact with other beigns with whom he shares this world.